Observations with Heatwatch to detect estrus by radiotelemetry in cattle - M.W. Smith; D.P. Hoffman; G.C. Lamb; Y. Kobayashi (Kansas Agricultural Experiment Station Research Reports, 1995)
In Experiment 1, the effectiveness of two estrus-detection methods (visual observation vs radiotelemetric, pressure-sensitive, rumpmounted devices [HeatWatch®]) were compared in heifers. A pressure sensitive device containing a battery-operated radio transmitter was affixed to the tailhead rump area of each of 41 heifers. Activation of the sensor sent a radiotelemetric signal to a microcomputer via a fixed radio antenna. Heifer identification, date, time of day, and duration of standing events were recorded. Estrus was synchronized, and heifers were observed visually for signs of estrus. Number of standing events during estrus, determined by the radiotelemetric device, averaged 50.1 ± 6.4 per heifer, with the duration of estrus ranging from 2.6 to 26.2 hr (average = 14 ± .8 hr). Number of standing events and duration of estrus were greater, but duration of standing events was similar, for heifers identified in estrus by both methods compared to those identified by the radiotelemetric device alone, indicating that heifers with a limited number of standing events and estrus of shorter duration were missed by visual observation. In Experiment 2, the average number of standing events during estrus was greater when estrus was induced early (days 6 to 9) in the cycle by PGF compared to those 2a induced later (after day 10) in the cycle. Regardless of when injections of PGF2α occurred during the cycle, duration of standing events and duration of estrus were unaffected. Radiotelemetric devices are useful in identifying a greater proportion of heifers in estrus (increased efficiency) compared to visual observation with similar accuracy.; Dairy Day, 1995, Kansas State University, Manhattan, KS, 1995;
Keywords: Dairy Day; 1995; Kansas Agricultural Experiment Station contribution; no. 96-106-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 742; Radiotelemetry; Pressure sensors; Estrus; Heifers; Heat Detection